Italian Agriculture, Industrialization and Commerce in the Chilean-Peruvian Frontier (Arica, 1885-1929) - Díaz, Alfonso; Pizarro , Elias Antonio; Soto, José (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2021)
This research focuses on economic activities developed by Italian immigrants settled in the Chilean city of Arica, located on the border with Peru. Analytically, it deals with Italian influence in the agricultural, industrial and commercial fields, based on state, municipal, judicial, hemerographic and oral sources. The conclusions underscore the importance of Italian immigration, which constituted an ethnic entrepreneurship that connected the Arican economy with international markets.